2001
DOI: 10.2337/diacare.24.5.909
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control Is a Predictor of Survival for Diabetic Patients on Hemodialysis

Abstract: OBJECTIVE -To investigate the impact of glycemic control on the survival of diabetic subjects with end-stage renal disease (ESRD) starting hemodialysis treatment. RESEARCH DESIGN AND METHODS-This single-center prospective observational study enrolled 150 diabetic ESRD subjects (109 men and 41 women; age at hemodialysis initiation, 60.5 Ϯ 10.2 years) at start of hemodialysis between January 1989 and December 1997. The subjects were divided into groups according to their glycemic control level at inclusion as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
5
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(148 citation statements)
references
References 27 publications
6
134
5
3
Order By: Relevance
“…This result suggests that HbA 1c ratios less than 7.3% are an adequate goal for glycaemic control in patients with diabetes on haemodialysis. This finding is consistent with the results of a previous report [12].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result suggests that HbA 1c ratios less than 7.3% are an adequate goal for glycaemic control in patients with diabetes on haemodialysis. This finding is consistent with the results of a previous report [12].…”
Section: Discussionsupporting
confidence: 94%
“…Morioka et al evaluated the clinical significance of glycaemic control in diabetic ESRD patients on haemodialysis, and revealed that, among patients with diabetes, those with poor glycaemic control (HbA 1c ≥7.5%) had a higher mortality risk than those with good control (HbA 1c < 7.5%) [12]. To date, however, two issues on glycaemic control and mortality have not been resolved, namely whether patients with diabetes and good glycaemic control have a higher mortality risk than those without diabetes, and whether there is any threshold of glycaemic control associated with a higher mortality risk among diabetes patients on haemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these trials excluded patients on hemodialysis, it has been argued that better glycemic control is key toward preventing DM‐related complications in this population 3, 7, 8, 9. In fact, surprisingly few studies have investigated the association between HbA 1c and clinical outcomes in the dialysis population 3, 10, 11, 12, 13, 14, 15, 16. Most of these studies focused only on all‐cause mortality as the outcome and were limited by small sample size and correspondingly low statistical power 11, 12, 13, 15…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have shown beneficial impact of predialysis glycemic control on survival after initiation of dialysis (6,7). In addition, limited studies showed an association of poor glycemic control with poor survival on chronic dialysis (8,9).…”
Section: In Diabetic Patients Glycemic Control Has An Essential Rolementioning
confidence: 99%